CRIMINAL ANALYSIS OF WAYS OF INVOLVING MINORS IN ILLEGAL ACTIVITIES: FROM TRADITIONAL PRACTICES TO CYBERCRIME (Bulletin of criminological association of Ukraine, 2025)
The article is devoted to the main ways of involving minors in illegal activities, in drunkenness, in begging, in gambling. Emphasis is placed on the possibility of their conditional division into two groups: those related and those not related to the use of violence or the threat of its use. Attention is focused on the choice by the offender of predominantly non-violent methods of involvement due to the peculiarities of the child's psyche, the ability to suggestibility, and vulnerability to negative influence from adults. It has been determined that the most common method of involvement in illegal activity is a proposal to commit a criminal offense, combined with psychological influence on a minor in order to arouse in him a conscious desire to engage in illegal activity. The active involvement of minors in criminal practices using the Internet, social networks, messengers and other online communication tools is emphasized. It has been established that this type of activity has become most widespread in connection with active military operations on the territory of Ukraine and the involvement of minors in politically motivated crimes related to intelligence, sabotage, terrorist and propaganda activities. The importance of studying the method of committing the involvement of minors in illegal activities as an interdisciplinary category studied within the framework of criminal law, forensics, criminology, operational and investigative activities, and legal psychology, as a basis for the formation of theoretical and practical recommendations for timely detection, high-quality investigation, effective prevention, and counteraction to the involvement of minors in illegal activities, is summarized.
Keywords: involvement in illegal activities; minor; mechanism; method; cyberspace; cybercrime; combating crime, war